An efficient optimal reconfiguration algorithm for FBRNs - Kamat, S.D. (Proceedings of 15th International Conference on Distributed Computing Systems, 1995)
We study a new network architecture called FBRN (FDDI-based reconfigurable network). An FBRN consists of multiple FDDI token rings and has the ability to reconfigure itself in the event of network faults. Thus, an FBRN has the potential to provide high available bandwidth even in the presence of numerous faults. Realization of this potential depends crucially on the choice of reconfiguration algorithm. We design and analyze a distributed reconfiguration algorithm for FBRNs. Our algorithm is optimal in the sense that it always produces a configuration that has the maximum available bandwidth possible for the given fault pattern. This algorithm has polynomial time complexity and hence can be efficiently implemented. We evaluate the algorithm's performance in terms of the available bandwidth in the network as a function of the number of faults.